1980
DOI: 10.1038/ki.1980.156
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular function in glycerol-induced acute renal failure

Abstract: The purpose of this study was to examine proximal and distal tubular function in rats with nonoliguric, myohemoglobinuric acute renal failure (ARF). ARF was induced with glycerol (50%, 10 ml/kg of body wt, i.m.), and renal function was studied 24 hours after glycerol or saline (controls) injection. Glycerol injection caused a 50 to 90% depression in GFR and a significant rise in blood urea nitrogen concentration. Animals with ARF exhibited glycosuria with normal blood sugar levels and a striking depression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…The administration of hypertonic glycerol solution i.m. has been used to induce acute renal insufficiency through rhabdomyolysis in rats 4,15–17 . In this model, renal insufficiency is thought to be caused by myoglobinuria and the formation of myoglobin and acid haematin casts 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of hypertonic glycerol solution i.m. has been used to induce acute renal insufficiency through rhabdomyolysis in rats 4,15–17 . In this model, renal insufficiency is thought to be caused by myoglobinuria and the formation of myoglobin and acid haematin casts 3 .…”
Section: Discussionmentioning
confidence: 99%
“…has been used to induce acute renal insufficiency through rhabdomyolysis in rats. 4,[15][16][17] In this model, renal insufficiency is thought to be caused by myoglobinuria and the formation of myoglobin and acid haematin casts. 3 However, although 20% of all glycerol is metabolised by the kidneys, 18 the direct effect of glycerol on the kidney has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In these early studies it was observed that the exposure of the kidney to a particular insult, uranyl nitrate, rendered the kidney resistant to subsequent challenges with the same nephrotoxin (9). Resistance to the same insult was thereafter noted with other, more clinically relevant insults including aminoglycoside antibiotics (12) and the glycerol model of acute renal failure (13,14), the latter representing a model of rhabdomyolysis. Resistance to renal injury was also recognized when the kidney was conditioned by dissimilar insults; for example, rats recovering from tubular injury induced by hypertonic glycerol were resistant to tubular damage induced by the tubular toxin, mercuric choride (15); rats treated with tubular toxins such as potassium dichromate (16) or mercuric chloride (17) exhibited reduced sensitivity to the nephrotoxic actions of gentamicin.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Westenfelder et al 3, found depressed glucose reabsorption, PAH extraction, and bicarbonates reabsorption, but no decrease in ammonium excretion in their in vivo study concerning glycerol-induced ATN. What is the reason for discrepancy?…”
mentioning
confidence: 86%